Blockchain based drug supply chain for decentralized network - Vijaykumar Bidve; Aryan Hamine; Sharwari Akre; Yash Ghan; Pakiriswamy Sarasu; Ganesh Pakle (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
The concept of supply and demand drives the scales of various markets in today’s world. When it comes to producing a quality product, the right kind of steps need to be taken to ensure that its quality can be supplemented with the process of its making. A supply chain is a business process that delineates the creation of a product. One such supply chain is the drug supply chain, focusing on the manufacturing and distribution of drugs. It is implied that there is an immense importance of traceability in the drug supply chain to ensure transparency amongst various actors and ultimately the end user. Improving on this crucial parameter allows drug supply chains to be carefully monitored and adhere to the various compliances from governing bodies. This work aim is to provide organizations with solutions that allow them to ameliorate the supply chain management. Using the blockchain technology, various transactions recorded in the supply chain can be checked against providing strong traceability and secure record-keeping. The positives that are provided by the blockchain transform the supply chain to a much more efficient and improved operation, impacting various facets of the process for the better.